Spirituality, beliefs, and religious practices of young Mexicans: coincidences and divergences between believers and nonbelievers - Salgado-Gutiérrez, Daniela (Church, Communication and Culture, 2025)
Youth is a stage in which vital principles are both questioned and reaffirmed; it is, therefore, both a challenge and an opportunity for personal growth and maturity. In today’s Mexico, young people comprise 24% of the population, or approximately 31.3 million as of 2023 (INEGI 2024). They constitute a population group whose convictions, values, ways of relating, and actions influence the present and the future at the social, cultural, and religious levels. This study examines the beliefs, values, and religious practices of this population group in Mexico, within the framework of a cross-cultural research project conducted in eight countries across four continents. Additionally, it describes how spirituality and faith are integrated into their lives, decision-making, aspirations, and social commitments. To this end, anthropological and pedagogical variables linked to the ethical and social life of believers and nonbelievers are analyzed. One of the contributions of this study is to emphasize the ethical and social discrepancies and similarities between the two groups and to formulate some pedagogical guidelines for the specific formation of Catholics and the transmission of the faith.